2004
DOI: 10.1002/ar.a.20124
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neuron‐specific markers by the vomeronasal neuroepithelium in six species of primates

Abstract: Vomeronasal organ (VNO) morphology varies markedly across primate taxa. Old World monkeys display no postnatal VNO. Humans and at least some apes retain a vestigial VNO during postnatal life, whereas the strepsirrhines and New World Monkeys present a morphologically well-defined VNO that, in many species, is presumed to function as an olfactory organ. Available microanatomical and behavioral studies suggest that VNO function in these species does not precisely duplicate that described in other mammalian taxa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 37 publications
4
52
0
Order By: Relevance
“…Recent immunohistochemical findings indicate that representatives of the two infraorders of Strepsirrhini, Lemuriformes and Lorisiformes, possess VNOs that express OMP (Dennis et al, 2004), a neuronal marker of mature olfactory and vomeronasal neurons (Farbman & Margolis, 1980;Margolis, 1980). Dennis et al (2004) also demonstrated that OMP was expressed at birth in species of the lemuriform genus Eulemur. The findings of the present study suggest this is also true of the lorisiform Otolemur garnettii.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent immunohistochemical findings indicate that representatives of the two infraorders of Strepsirrhini, Lemuriformes and Lorisiformes, possess VNOs that express OMP (Dennis et al, 2004), a neuronal marker of mature olfactory and vomeronasal neurons (Farbman & Margolis, 1980;Margolis, 1980). Dennis et al (2004) also demonstrated that OMP was expressed at birth in species of the lemuriform genus Eulemur. The findings of the present study suggest this is also true of the lorisiform Otolemur garnettii.…”
Section: Discussionmentioning
confidence: 99%
“…Dennis et al (2004) hypothesized that, with regard to BT and OMP expression, primate vomeronasal sensory neurons follow a developmental program similar to that of sensory neurons of the rat main olfactory epithelium. In those cells, BT is expressed first followed by OMP expression and a down regulation of BT in the cell body (Lee & Pixley, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the significance of this difference is presently unclear, it may relate to different characteristics of the neuronal populations recently described for marmosets and tamarins. In fact, S. geoffroyi may have nonfunctional VNOs as adults based on the near absence of olfactory marker protein (OMP) expression in the VNO epithelium; OMP is ubiquitously present in the VNNE of C. jacchus (Dennis et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The organ and bulb are smaller and extremely variable in platyrrhines (Stephan et al, 1981Baron et al, 1983;Dennis et al, 2004) and rudimentary in adult catarrhines (Stephan et al, 1981Baron et al, 1983). This suggests that pheromonal communication may not be as important to platyrrhines compared to strepsirrhines and may be even less important in catarrhines than in platyrrhines.…”
Section: Anatomical Evidencementioning
confidence: 99%